Peran AI dalam Perspektif Fotografi Seni - Marventyo Amala (Rekam, 2025)
The Role of AI from the Perspective of Art Photography. Art photography is a medium of visual expression that emphasizes aesthetics, concepts, and subjectivity. With the advancement of technology, Artificial Intelligence (AI) has begun to play a significant role in the creation of artistic photographic works. This research aims to examine how AI influences the practices and values within contemporary art photography. Using a literature review and visual analysis approach, this study explores the application of AI in generating artistic images, processing visual aesthetics, and fostering creative collaboration between photographers and machines. The findings indicate that AI is not merely a technical tool, but also an opener of new opportunities for experimenting with form, visual narratives, and the creation of imaginative realities. However, critical challenges also arise concerning originality, ownership of work, and the artist's identity in the era of visual automation. Therefore, a deep understanding of AI's role in art photography is essential to maintain a balance between technological innovation and the artistic values that underpin the practice of photography itself.